Development of a nomogram combining multiparametric magnetic resonance imaging and PSA‐related parameters to enhance the detection of clinically significant cancer across different region. Issue 5 (31st January 2022) - Zhou, Zhien; Liang, Zhen; Zuo, Yuzhi; Zhou, Yi; Yan, Weigang; Wu, Xingcheng; Ji, Zhigang; Li, Hanzhong; Hu, Mengyao; Ma, Lin
Abstract: Objective: Prostate cancer (PCa) is the most prevalent cancer among males. This study attempted to develop a clinically significant prostate cancer (csPCa) risk nomogram including Prostate Imaging‐Reporting and Data System (PI‐RADS) score and other clinical indexes for initial prostate biopsy in light of the different prostate regions, and internal validation was further conducted. Patients and Methods: A retrospective study was performed including 688 patients who underwent ultrasound‐guided transperineal magnetic resonance imaging fusion prostate biopsy from December 2016 to July 2019. We constructed nomograms combining PI‐RADS score and clinical variables (prostate‐specific antigen [PSA], prostate volume (PV), age, free/total PSA,  and PSA density) through univariate and multivariate logistic regression to identify patients eligible for biopsy. The performance of the predictive model was evaluated by bootstrap resampling. The area under the curve (AUC) of the receiver‐operating characteristic (ROC) analysis was appointed to quantify the accuracy of the primary nomogram model for csPCa. Calibration curves were used to assess the agreement between the biopsy specimen and the predicted probability of the new nomogram. The χ 2 test was also applied to evaluate the heterogeneity between fusion biopsy and systematic biopsy based on different PI‐RADS scores and prostate regions. Results: A total of 320 of 688 included patients were diagnosed with csPCa. csPCa was defined as Gleason score ≥7. The ROC and concordance‐index both presented good performance. The nomogram reached an AUC of 0.867 for predicting csPCa at the peripheral zone; meanwhile, AUC for transitional and apex zones were 0.889 and 0.757, respectively. Statistical significance was detected between fusion biopsy and systematic biopsy for PI‐RADS score >3 lesions and lesions at the peripheral and transitional zones. Conclusion: We produced a novel nomogram predicting csPCa in patients with suspected imaging according to different locations. Our results indicated that PI‐RADS score combined with other clinical parameters showed a robust predictive capacity for csPCa before prostate biopsy. The new nomogram, which incorporates prebiopsy data including PSA, PV, age, and PI‐RADS score, can be helpful for clinical decision‐making to avoid unnecessary biopsy.